Influences of Fermented Corn Straw Fiber on Performance and Nutrient Utilization in Different Breeds of Finishing Pigs - Rui Han; Feng Yong; Xin Fang; Chun Zhang; Haitian Yang; Dongsheng Che; Hailong Jiang (Animals)
This study aimed to explore the effects of dietary fiber level and breed on the growth performance, nutrient utilization, intestinal morphology, slaughter performance, and meat quality of finishing pigs using fermented corn straw (FCS) as the fiber source. The experiment employed a 2 × 4 factorial design, selecting 96 Songliao Black (SLB) and Duroc × Landrace × Yorkshire (DLY) crossbred finishing pigs (a total of 192 pigs, with an initial body weight of 60.52 ± 4.59 kg) randomly assigned by breed to four dietary treatment groups (A: 2.92% crude fiber; B: 4.82% crude fiber; C: 6.86% crude fiber; D: 9.01% crude fiber). The results showed that DLY finishing pigs had higher final weight (FW), average daily gain (ADG), and average daily feed intake (ADFI) in both finishing stages 1 and 2 compared to SLB pigs (p < 0.05), while the ratio of feed to weight gain (F/G) showed no significant differences (p > 0.05). Compared to the basal diet, increasing the dietary fiber level to 4.82% improved FW and ADG in both SLB and DLY finishing pigs (p < 0.05) and reduced F/G (p < 0.05). Additionally, SLB finishing pigs had lower ether extract (EE) digestibility but higher crude fiber (CF) and acid detergent fiber (ADF) digestibility than DLY (p < 0.05). Dietary fiber level and breed exhibited an interaction effect on dry matter (DM) and crude protein (CP) digestibility in finishing pigs (p < 0.05). At a dietary fiber level of 4.82%, villus height, crypt depth in the jejunum, and cecal volatile fatty acid (VFA) concentrations were increased in both SLB and DLY finishing pigs (p < 0.05). Dietary fiber level and breed showed an interaction effect on cecal VFA production in finishing pigs (finishing stage 1; p < 0.05). The dietary fiber level of 4.82% increased loin eye area (LA) (p < 0.05) and decreased backfat thickness (BT) (p < 0.05) in both SLB and DLY finishing pigs. Dietary fiber level and breed had an interaction effect on LA in finishing pigs (p < 0.05). SLB pigs had higher muscle redness (a*), shear force, and contents of crude protein (CP), EE, saturated fatty acid (SFA), and polyunsaturated fatty acids (PUFA) than DLY (p < 0.05). Increasing the dietary fiber level improved pH24h and reduced drip loss and shear force in both SLB and DLY finishing pigs (p < 0.05). Dietary fiber level and breed showed an interaction effect on pig meat color and drip loss (p < 0.05). In conclusion, FCS is a beneficial source of dietary fiber for SLB and DLY pigs. Its proper addition can enhance the growth performance, carcass traits, and meat quality in fattening pigs.